Strategies for the implementation of UDL in mathematics: The case of an Online Mathemathical Olympiad Course - Rodríguez Luis, Daniel José; Roldán López, Jorge (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this paper, we provide various strategies to encourage student motivation and participation in the creation of educational videos on problem solving in Mathematical Olympiads, sharing their proposals on virtual platforms. Likewise, we present methodologies that allow the development of linguistic, problem-solving and initiative skills of the students through the creation of their own videos, as well as a practical use of the Genial.ly platform for the provision of multiple formats (audiovisual, textual , etc.) that make easier the inclusion of people with hearing needs.